Relationship Between Risk Factors Affecting the Occurrence of Diabetic Ulcer Classification in Patients with Type 2 Diabetes Mellitus in Kendari City Hospital - Andi Nur Meilia Jufriyani; Tomy Nurtamin; Adry Leonardy Tendean (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
Background. Diabetes mellitus is a metabolic disease caused by the body being unable to produce insulin hormone or peripheral insulin resistance. This chronic hyperglycemia condition can cause complications of diabetes mellitus, one of which is diabetic ulcers. Diabetic ulcer is a chronic complication of diabetes mellitus caused by several factors that can affect it. Some of these factors are age, comorbidities, length of suffering and drug compliance which play a role in causing diabetic ulcers. This study aims to determine the relationship between several factors that cause the classification of diabetic ulcers in patients with type 2 diabetes mellitus at Kendari City Hospital. Methods. This study was conducted with observational analytic method with cross sectional approach conducted at Kendari City Hospital with 62 respondents. Data were collected and analyzed using Fischer's exact test with a significant value of p≤ 0.05. Results. This study shows that there is a significant relationship between the age variable and the classification of diabetic ulcers with a p-value of 0.04, a significant relationship between comorbidities and the classification of diabetic ulcers with a p-value of 0.00, there is no significant relationship between the duration of DM and the classification of diabetic ulcers with a p-value of 0.15, and there is a significant relationship in drug compliance and the classification of diabetic ulcers with a p-value of 0.00. Conclusion. There is a significant relationship between three risk factors such as age, comorbidities, and medication compliance with the occurrence of diabetic ulcer classification. And there is no significant relationship between the duration of DM and the occurrence of diabetic ulcer classification in type 2 diabetes mellitus patients at Kendari City Hospital. This underlines the importance of avoiding factors that can cause complications of diabetes mellitus in the form of diabetic ulcers.